Contributions to the Understanding of the Bloom Dynamics of Pyrodinium bahamense var. compressum : A Toxic Red Tide Causative Organism - Azanza, Rhodora (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Pyrodinium bahamense var. compressum has been the primary organism responsible for the toxic red tide episodes which have been recurring in Manila Bay, Philippines since 1988. The life history of the species has been elucidated through encystment-excystment studies in vitro , from which its obligatory dormancy has been demonstrated. Cyst-mapping studies have shown that this life stage of the organism occurs relatively higher in the Bataan and Cavite areas where the greater number of red tide occurrences have also been reported. A cyst-based model has been developed as an initial step in understanding the role of physical processes in the development, occurrence/recurrence, and ultimately, advancement of Pyrodinium red tides in Manila Bay. To help mitigate or prevent the negative impacts of toxic red tides, particularly in Manila Bay, regular closure of shellfish harvest in areas affected by Pyrodinium bloom should be considered, based on long term monitoring and research data sets.